The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21037/apm-21-2236
|View full text |Cite
|
Sign up to set email alerts
|

Negative anti-neutrophil cytoplasmic antibodies and eosinophilic granulomatosis with polyangiitis accompanied by cough variant asthma: a case report

Abstract: is generally agreed that EGPA is an anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), which is positive for ANCA in approximately 50-70% of cases (2,3), especially in patients with glomerulonephritis (4). The time from disease activity to diagnosis was shorter in ANCA positive patients than in ANCA negative patients, and the inflammatory response was more severe. EGPA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The patient usually has a history of chronic asthma, longstanding rhinitis, recurrent sinusitis, otitis media, nasal obstruction, and nasal polyposis. Asthma is one of the most common associations of EGPA and has several types which include allergic asthma mediated by IgE, aspirin-exacerbated respiratory disease, exercise-induced asthma, non-allergic asthma often triggered by viral upper respiratory tract infections or no apparent cause, and cough variant asthma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient usually has a history of chronic asthma, longstanding rhinitis, recurrent sinusitis, otitis media, nasal obstruction, and nasal polyposis. Asthma is one of the most common associations of EGPA and has several types which include allergic asthma mediated by IgE, aspirin-exacerbated respiratory disease, exercise-induced asthma, non-allergic asthma often triggered by viral upper respiratory tract infections or no apparent cause, and cough variant asthma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was ANCA negative with high levels of eosinophils in the bone marrow and peripheral blood with respiratory, cutaneous, neural, and skeletal manifestations. The possible mechanism of organ injury is eosinophil-associated vascular occlusion leading to ischemia and eosinophil-associated tissue damage [ 12 ]. In the vasculitic phase of the disease, histopathology shows eosinophilic infiltration of the vessel walls and necrotizing eosinophilic granuloma in extravascular tissue [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been reported to be elevated in both antineutrophil cytoplasmic antibody-negative and -positive eosinophilic granulomatosis with polyangiitis. Also, hsCRP was found to be higher in Wegener’s granulomatosis cases that are in relapse, and serial CRP measurement fills the urgent need for an objective index of the activity of this disease [ 668 , 669 , 670 , 671 ]. Apart from Kawasaki disease, in which data are contrasted, some authors believe that arteriosclerosis is an autoimmune condition; hsCRP has been correlated with disease severity, and a study found that SNPs affect arterial pulse wave velocity in healthy people [ 672 , 673 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%